Evaluación de riesgos en la construcción del asfaltado - primera etapa de la via Chasualo barrio Nuevo, cantón Salcedo, provincia Cotopaxi - Carrillo Vélez, Edwin Xavier (2016)
The identification and assessment of the factors risk in each one of the jobs, it plays a fundamental paper to preserve the safety and health of workers who provide services in the construction of road works for the company CV CONSTRUCCIONES. It will apply the general risks assessment, methodology proposed by the National Institute for Occupational Safety and Health (INSHT), which allows assess risks according to the work activities, identification risks, estimate and risks valoration. The risks evaluation permits to determine decisions to see with the necessity or not to perform preventive actions or corrective depending on the degree of importance with qualifies a risk factor present in the workplace. The project will generate great importance in the social part for the workers because it will promote a preventive culture to care their health, since people to know what risks they are exposed in their workplace will become aware of future consequences these may create for health. In the economic part will allow the institution avoids costs generated by accidents and occupational diseases, that workers may suffer if it is not taken preventive actions or corrective prevention risks.